2020
DOI: 10.21203/rs.3.rs-24120/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The diagnostic power of CD117, CD13, CD56, CD64, and MPO in rapid screening acute promyelocytic leukemia

Abstract: Objective: The same immuno-phenotype between HLA-DR-negative acute myeloid leukemia (AML) and acute promyelocytic leukemia (APL) causes APL rapid screening to become difficult. This study aimed to identify the associated antigens for APL and the best model in clinical uses.Results: A total of 36 APL (PML-RARA+) and 29 HLA-DR-negative non-APL patients enrolled in this study. When a cut-off point of 20% events was applied to define positive or negative status, APL and non-APL patients share a similar immuno-phen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Another aspect that may aid in distinguishing between these two AML is expression of myeloperoxidase (MPO), as has also been found by others. 5 In this cohort, expression of MPO was lower in NPM1 mut AML than in APL (median [interquartile range] MFI (arbitrary units) of 4.9 [2.1 to 20] in NPM1 mut AML vs 48 [12 to 85] in APL, Mann-Whitney test, P value .0082; Figure 3). The MPO AUROC curve in this cohort was 0.83 (95% CI: 0.67-0.99, Figure 3), and the best cutoff was 9.…”
Section: E T T E R T O T H E E D I T O R On the Distinction Between A...mentioning
confidence: 77%
See 1 more Smart Citation
“…Another aspect that may aid in distinguishing between these two AML is expression of myeloperoxidase (MPO), as has also been found by others. 5 In this cohort, expression of MPO was lower in NPM1 mut AML than in APL (median [interquartile range] MFI (arbitrary units) of 4.9 [2.1 to 20] in NPM1 mut AML vs 48 [12 to 85] in APL, Mann-Whitney test, P value .0082; Figure 3). The MPO AUROC curve in this cohort was 0.83 (95% CI: 0.67-0.99, Figure 3), and the best cutoff was 9.…”
Section: E T T E R T O T H E E D I T O R On the Distinction Between A...mentioning
confidence: 77%
“…6 This fact has been also reported by other groups. 5 It is also of note that all five cases described by Arana Rosainz et al, 1 CD4 was expressed by leukemic cells. Expression of this marker is considered uncommon in APL, but some authors 7 have found CD4 to be expressed in as much as a 57.5% of APL, a percentage similar to that observed in NPM1 mut AML.…”
Section: F I G U R Ementioning
confidence: 83%
“…In this case, it was rst considered as acute promyelocytic leukemia (APL) when blood and marrow smears showed a mass of coarse granules in the cytoplasm of abnormal cells, although the Auer body was not found. However, the subsequent laboratory results of marrow aspirate or biopsy were all negative for MPO molecules, t (15; 17) (q22; q21), and RARα rearrangement, which were the classical diagnosis criteria for APL [28,29], so that the disease was excluded. Myelomastocytic leukemia (MML) is another major differential diagnosis to MCL and is also considered an advance myeloid neoplasm with excess blasts accompanied by abnormal MCs morphologically, which fails to meet the criteria of SM to distinguish from MCL [14,30].…”
Section: Discussionmentioning
confidence: 99%
“…The STAT5A/B overexpression may contribute to the disruption of the natural mechanisms of programmed cell death [81]. It is postulated that STAT5 mutations may be solely responsible for the neoplastic transformation of defective cells [93,100,101]. Autoactivating molecular defects concerns the STAT5B gene much more often than STAT5A.…”
Section: Stat Gene Mutations In Lymphoproliferative Neoplasmsmentioning
confidence: 99%